Proportion of neonatal readmission attributed to length of stay for childbirth: a population-based cohort study. Issue 9 (14th September 2016) - Metcalfe, Amy; Mathai, Matthews; Liu, Shiliang; Leon, Juan Andres; Joseph, K S
Abstract : Objective: Most literature on length of stay (LOS) for childbirth focuses on 'early' discharge as opposed to 'optimal' time of discharge and has conflicting results due to heterogeneous definitions of 'early' discharge and differing eligibility criteria for these programmes. We aimed to determine the LOS associated with the lowest neonatal readmission rate following childbirth by examining the incidence pattern of neonatal readmission for different LOS using the Kitagawa decomposition. Design: Retrospective cohort study using administrative hospitalisation data. Setting: Canada (excluding Quebec) from 2003 to 2010. Patients: Term, singleton live births without congenital anomalies. Interventions: LOS for childbirth. Main outcome measure: Neonatal readmissions within 30 days of birth. Results: 1 875 322 live births were included. Neonatal LOS peaked at day 1 (47.3%) after vaginal birth and day 3 (49.3%) following caesarean section; 4.2% of infants were readmitted following vaginal birth and 2.2% after caesarean section. In 2008–2010, most readmissions occurred among infants discharged in the first 2 days (83.8%) following a vaginal birth and among infants discharged in the first 3 days (81.7%) following a caesarean birth. Readmissions increased from 4.1% in 2003–2005 to 4.6% in 2008–2010 among vaginal births and from 2.0% to 2.4% among caesarean births and occurred mostly due to changes in the day-specific readmission rates and not due to reductions in LOS. Conclusions: Patterns of readmission suggest that readmission rates are lowest following a 1–2-day stay following a vaginal birth and a 2–4-day stay following a caesarean birth given the outpatient support in the community.